2022
DOI: 10.1002/mds.29218
|View full text |Cite
|
Sign up to set email alerts
|

Gaps, Controversies, and Proposed Roadmap for Research in Poststroke Movement Disorders

Abstract: Poststroke movement disorders (PSMDs) are a common cause of secondary movement disorders. Although prior studies have highlighted the clinical spectrum and phenomenology of PSMDs, there are many knowledge gaps worth addressing. Some of the most important include lack of clinical definitions, variable stroke symptom latencies, and lack of biomarkers for vulnerability for or resilience against developing PSMDs. Collectively, the association between stroke localization and phenomenology is less than 30%, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
(245 reference statements)
0
4
0
Order By: Relevance
“…Neither the clinical characteristics at baseline nor the site of the ischemic lesion significantly correlated with the development of PMDs, possibly due to the limited sample size. A possible link between PMD phenomenology and ischemic lesion site was recently proposed using a functional network-based rather than a structural approach to stroke localization [5,46], which may constitute a promising future study direction. The higher NIHSS score at discharge along with greater 3-month mRS and 6-month UPDRS II scores in the group who developed a PMD may suggest that patients with more clinically severe AIS are at higher risk for developing PMDs, although such results need to be confirmed in a larger population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the clinical characteristics at baseline nor the site of the ischemic lesion significantly correlated with the development of PMDs, possibly due to the limited sample size. A possible link between PMD phenomenology and ischemic lesion site was recently proposed using a functional network-based rather than a structural approach to stroke localization [5,46], which may constitute a promising future study direction. The higher NIHSS score at discharge along with greater 3-month mRS and 6-month UPDRS II scores in the group who developed a PMD may suggest that patients with more clinically severe AIS are at higher risk for developing PMDs, although such results need to be confirmed in a larger population.…”
Section: Discussionmentioning
confidence: 99%
“…Movement disorders secondary to acute ischemic stroke (AIS) of the basal ganglia (BG) often occur with variable latency [1] and present with a variety of symptoms [2][3][4][5]. Both hyperkinetic and hypokinetic post-stroke movement disorders (PMDs) can be observed in patients following ischemic injury of the BG, owing to their key role in motor function control [1,3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, however, MMD is more associated with ischemic events, particularly in pediatrics; presentation with movement disorders is rare, with an estimated frequency of 3–6% ( 2 , 3 ). Its pathophysiological mechanism is still poorly understood; some have suggested that the choreoathetosis in MMD is a result of active ischemic changes affecting the excitatory–inhibitory circuits between the basal ganglia and the neocortex ( 6 ). A small literature review published in Frontiers in Neurology ( 16 ) revealed that hypermetabolism noticed in the pathway of basal ganglia-thalamocortical circuits using an 18F-FDG PET may explain the MMD-induced chorea, rather than the striatal hypoperfusion previously detected by SPECT ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive thyroid hormones contribute to the dysregulation of neurotransmitters in basal ganglia-thalamocortical circuits ( 5 ). Moyamoya disease is responsible for ischemic changes affecting the excitatory–inhibitory circuits between the basal ganglia and the neocortex ( 6 ). In management, despite medical correction of the state of thyrotoxicosis, a timely combination of steroids may not only synergize the anti-thyroid effect but also may be a possible curative treatment for involuntary movement disorders ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%